DESIGNING AN INFORMATION RESOURCE TO EXPLAIN DIAGNOSTIC LUMBAR PUNCTURE AND PROMOTE BEST PRACTICE. Issue 11 (14th October 2015) - Thomson, Alison; Davis, Angharad; Paterson, Adam; Giovannoni, Gavin; Schmierer, Klaus
Abstract : Introduction: The lumbar puncture (LP) procedure is an important test in neurological practice. Appropriate information is key to both preparing patients for this invasive procedure and facilitating use of atraumatic LP needles to minimize adverse effects such as local pain and post-LP headache. Methods: A cross-disciplinary team (designers, clinicians and people with multiple sclerosis (pwMS)) developed a website to explain the LP procedure at The Royal London Hospital (Barts Health NHS Trust, UK). User testing was carried out to review both the visual design and functionality of the resource for people with visual and cognitive limitations. Results: After successful testing www.clinicspeak.com/LumbarPuncture is being used in the informed consent process for clinical trials involving pwMS at our institution and is being piloted in our day unit and A&E departments. The website includes what to expect, how to deal with adverse effects, why cerebrospinal fluid is examined and information on the atraumatic needle. Conclusion: The resource provides an appropriate way of communicating sensitive, yet important information to patients. It also demonstrates an innovative way of spreading best practice and encourages the widespread adoption of atraumatic needles for LP in both clinical and research settings. The resource will be demonstrated at the meeting.